Cross-resistance to antibiotics of Escherichia coli in the inpatient installation of general regional hospital “X” Bali, Indonesia - Mahaputra, I Putu Yudistira; Sanjaya, Dwi Arymbhi; Meriyani, Herleeyana; Juanita, Rr Asih; Siada, Nyoman Budiartha; Kamalia, Made Gek Adisti; Adrianta, Ketut Agus; Noviani, Lusy (Pharmaciana, 2025)
Escherichia coli (E. coli) is a critical-priority group of MDR bacteria and its spread can occur in hospital inpatient settings. Several studies showed that antibiotics consumption for inpatients can cause E. coli resistance to other antibiotics called cross-resistance. The aim of this study to determine the cross-resistance in E. coli to antibiotics in the inpatient installation of the regional general hospital "X" in Bali, Indonesia by analyzing the relationship between the antibiotic consumption and the percentage of antibiotic resistance of E. coli. This research is an ecological study with the independent variable is the antibiotics consumption defined as defined daily doses/100 bed-days and the dependent variable is the percentage of E. coli resistance during 2017-2020. The correlation between the level of antibiotic consumption and the percentage of E. coli resistance to antibiotics was analyzed using the Pearson correlation tests. The results showed that the consumption of tetracycline had a significant correlation with increased resistance of E. coli to meropenem and piperacillin-tazobactam (r=0.8-1.0; p<0.05). This showed that there is cross-resistance in E. coli. This incident is associated with selective pressure, horizontal and vertical gene transfer in E. coli. The consumption of tetracycline, apart from inducing the production of the tet gene which is the cause of resistance to tetracycline, can also induce the production of resistance genes to broad-spectrum beta-lactam antibiotics such as piperacillin-tazobactam and meropenem.